2021
DOI: 10.1016/j.dld.2021.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Functional abdominal pain disorders and patient- and parent-reported outcomes in children with inflammatory bowel disease in remission

Abstract: Background: Chronic abdominal pain occurs frequently in pediatric patients with inflammatory bowel disease (IBD) in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…A recent US survey, based on the Rome IV diagnostic criteria, found that 17% of children and adolescents in the United States had FAPDs (1). FAPDs can present as isolated disorders or overlap with organic diseases such as inflammatory bowel disease (IBD) (2). Patients with FAPDs report notable reduction in quality of life (3).…”
mentioning
confidence: 99%
“…A recent US survey, based on the Rome IV diagnostic criteria, found that 17% of children and adolescents in the United States had FAPDs (1). FAPDs can present as isolated disorders or overlap with organic diseases such as inflammatory bowel disease (IBD) (2). Patients with FAPDs report notable reduction in quality of life (3).…”
mentioning
confidence: 99%
“…The most recent study reporting on the prevalence of FAPDs in children with IBD in remission was published by Tran et al in 2021. 16 A total of 102 patients were recruited based on the study inclusion remission criteria, defined by physician's global assessment and features that include the absence of each of the following: >3 stools/day, blood in stools, nocturnal stools, ongoing steroid therapy, recurrence of disease or optimization of treatment in the last 3 months. Patient-and parent-reported Rome III Diagnostic Questionnaire for the Pediatric Functional Gastrointestinal Disorders (Fr-qPGS) were utilized to diagnose FGIDs, which included FAPDs and other subclassifications of FGIDs.…”
Section: Resultsmentioning
confidence: 99%
“… 13 The other three studies included patients with either CD or UC, as well as patients with IBD‐U in the study by Tran et al . 14 , 15 , 16 Overall, the prevalence of IBS in children with IBD in remission ranged between 3.9 and 16.1%, while the prevalence of FAPDs in children with IBD in remission ranged between 9.6 and 29.5%. The prevalence of functional abdominal pain was found to be 10.3% based on the result by Zimmerman et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations